PENGARUH KOMPETENSI PROJECT MANAGER TERHADAP KEBERHASILAN PROYEK KONSTRUKSI GEDUNG APARTEMEN X - Nedya Sonelma; I Ketut Sucita (Construction and Material Journal, 2022)
One of the factors in achieving project success is influenced by the role of a project manager. Project managers (PM) as project leaders are required to have and fulfill the competencies needed to ensure the realization of project management, so that the project is said to be successful. The competency of a project manager according to the Guide to the Project Management Body of Knowledge (PMBOK® Guide) Sixth Edition (2017) can be measured by three aspects known as The PMI Talent Triangle which consists of Technical Project Management, Leadership Skills, and Strategic and Business Management. This research aims to identify the competence of a project manager whose dominant influence on the success of the project and determine the magnitude of the effect of the application of project manager competencies on the success of construction project. Data were collected through a survey using a questionnaire which was distributed to a total of 30 respondents who are employees of the project. Data analysis was performed by multivariate regression analysis. From the results of the analysis, the regression coefficient values for the Technical Project Management, Leadership Skill and Strategic and Business Management variables were 0.423, 0.097, and 0.437. From the results of the coefficient of determination test, it was found that the influence of project manager competencies on the success of building construction projects was 44%. Keywords: Competency, Construction, Project Manager, Success.